Genome-wide association studies and traditional Chinese medicine in hyperuricemia: current evidence and mechanistic insights - Yang, Le; Liu, Jing; Luo, Shengping; Deng, Yihui (Frontiers in Pharmacology, 2026)
Hyperuricemia is a significant risk factor for gout, cardiovascular disease, and chronic kidney disease, and its global prevalence has continued to rise. Genome-wide association studies (GWAS) have made significant advances in elucidating the genetic basis of serum uric acid levels, identifying key loci such as SLC2A9, ABCG2, SLC22A12, GCKR, and HNF4A, while also revealing population heterogeneity and gene–environment interactions. Concurrently, traditional Chinese medicine (TCM) has demonstrated multi-component, multi-pathway regulatory effects on uric acid production, renal and intestinal excretion, inflammatory responses, and gut microbiota. This review summarizes recent GWAS advances in hyperuricemia and compiles experimental and mechanistic studies on TCM regulation of uric acid homeostasis over the past 5 years. Furthermore, the discussion section outlines current limitations in both GWAS and TCM research, proposes potential connections between them in specific regulatory processes, and explores possible directions for future mechanistic studies and the development of intervention strategies.